Multiple developmental pathways in organisms with developmentally complex life cycles - Fusco, Giuseppe; Minelli, Alessandro (Frontiers in Cell and Developmental Biology, 2025)
One aspect under which an organism’s life cycle can be considered complex is when the very same organism can undertake, or obligatorily undertakes, multiple developmental pathways. Examples are organisms with alternation of generations, like most plants, or organisms with reproductive and/or developmental options, like many marine invertebrates. With a broad taxonomic coverage across the eukaryotes, we survey these developmentally complex life cycles, presenting selected case studies to illustrate the relationships between the diverse developmental pathways within the same organism for what concerns morphogenesis and gene expression. We highlight the deep connections between the different types of cycles and show their relationship with phenotypic plasticity, sexual dimorphism and ecological adaptation. The collected materials and organized concepts can provide the basis for future investigations on the disparity of complex life cycles and their evolution across the tree of life.